Facile synthesis of CoFePO4 on eggshell membrane for oxygen evolution reaction and supercapacitor applications. Issue 24 (15th December 2022) - Manzoor, Sumaira; Abid, Abdul Ghafoor; Aman, Salma; Abdullah, Muhammad; Rashid, Abdul Rasheed; Ali, Hazim M.; Ali, Tarik E.; Assiri, Mohammed A.; Ashiq, Muhammad Naeem; Taha, T.A.
Abstract: The rapid consumption and utilization of fossil fuels create a polluted environment and energy depletion. However, there is an urgent need to develop an alternative source for producing energy sources and energy storage devices. In this study, CoFePO4 is designed by a simple reduction method to address energy production and energy shortage issues. The structure, phase purity, sample orientation, textual characteristics and morphology are evaluated through different techniques. The electrocatalytic activity of the fabricated electrode material was investigated and the deposited eggshell membrane act as a working electrode in a basic medium. The fabricated electrode material exhibited the 1685 F g −1 specific capacitance with 79.45 Wh kg −1 specific energy density with a current density of 0.02 A g −1 . The oxygen evolution reaction (OER) performance displays a smaller overpotential equivalent to 285 mV with a smaller 53 mv dec −1 tafel slope value, and also the electrocatalyst shows good stability for 14 h. The experimental results revealed that the CoFePO4 nanoflakes are a potential candidate for energy conversion systems and oxygen evolution reaction.